Non-Invasive Wearables in Inflammation Monitoring: From Biomarkers to Biosensors - Tingting Wu; Guozhen Liu (Biosensors)
Quantifying inflammation plays a critical role in understanding the progression and development of various diseases. Non-invasive or minimally invasive wearable biosensors have garnered significant attention in recent years due to their convenience, comfort, and ability to provide continuous monitoring of biomarkers, particularly in infectious diseases and chronic diseases. However, there are still areas for improvement in developing reliable biosensing devices to detect key inflammatory biomarkers in clinically relevant biofluids. This review first introduces common biofluids with a focus on the most clinically significant inflammatory biomarkers. Specifically, it discusses the challenges encountered in extracting and detecting analytes in these biofluids. Subsequently, we review three popular types of non-invasive wearable biosensors for inflammation monitoring (microneedle patches, flexible electronic skins, and textile-based sensors). The design and operational considerations of these devices are analyzed, followed by an exploration of the information processing approaches employed during data processing. Finally, we envision future opportunities by guiding the development and refinement of non-invasive or minimally invasive wearable biosensors for continuous inflammation monitoring in chronic diseases.